In-Vitro Apatite Growth On Porous Â-Tricalcium Phoshpate Scaffolds Coated With PHVB - Mustafa, Zaleha; Ishak, Nor Fatiha; Othman, Radzali; Ahmad, Nor Naimah Rosyadah; Abd Rahim, Toibah; Sheikh Md Fadzullah, Siti Hajar; Tanner, K. Elizabeth (Penerbit Universiti Teknikal Malaysia Melaka, 2018)

(untitled)
The bioactive properties of polyhydroxybutyrate-co-valerate (PHBV) coated beta-tricalcium phosphate (β-TCP) have been studied invitro. Porous β-TCP scaffolds have been prepared using a template method and sintered at 1450 °C.The bio ceramics were then coated with PHBV solution before being immersed for 6 weeks in a simulated body fluid (SBF)at 37°C.At the end of the immersion time, insignificant changes in the SBF pH value was observed, suggesting good stability against hydrolytic degradation. X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) analyses revealed the presence of apatite.Morphological analysis by SEM showed the formation of apatite crystals in the form of flakes and globular deposits on the scaffold surface.This bonelike apatite indicates good biological activity of the bio ceramics scaffold with PHVB coating suggesting that the composite has potential for bone tissue engineering applications.